Association of HLA genotypes with phenytoin induced severe cutaneous adverse drug reactions in Thai children - Wiparat Manuyakorn (2020)
© 2020 Elsevier B.V. Purpose: Phenytoin (PHT) is a common causative drug for severe cutaneous adverse drug reactions (SCARs) in children. SCARs, including drug reaction with eosinophilia and systemic symptoms (DRESS), Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN), are associated with a variation in HLA genotypes. Blood screening for specific HLA allele before PHT prescription would help in the reduction of the incidence of PHT induced SCARs. This study was to investigate the association between variations of HLA genotypes and PHT induced SCARs in Thai children. Methods: Cases were Thai children aged between 0–18 years diagnosed with SCARs from PHT. Control groups were Thai children of corresponding age who had taken PHT for a least 12 weeks without any hypersensitivity reaction and healthy population controls. Blood samples from both groups were collected for HLA genotyping using a reverse-sequence specific oligonucleotide (SSO) probes method. Carrier rates of HLA alleles were compared between 22 cases (17 DRESS and 5 SJS-TEN), 60 tolerant controls and 649 population controls. Results: Two HLA alleles includingHLA-B*51:01 and HLA-C*14:02 were significantly associated with PHT induced DRESS (OR 5.83; 95 % CI 1.36–25.00, p = 0.022 and OR 5.85; 95 % CI 1.16–29.35, p = 0.039). HLA-B*38:02 was significantly associated with PHT induced SJS-TEN (OR12.67; 95 % CI 1.50–106.89, p = 0.044). Haplotype analysis demonstrated the association of HLA haplotype A*11:01-B*51:01-C*14:02 and PHT induced DRESS compared to tolerant controls and the healthy population control group (OR 8.92; 95 % CI 1.47–54.02, p = 0.019, and OR 10.2; 95 % CI 3.04–34.21, p = 0.002). HLA haplotype B*38:02-C*07:01 in PHT induced SJS-TEN was significantly higher than those in tolerant controls and the healthy population control group (40 % vs 3.3 % vs 0.3 %; OR 19.33; 95 % CI 1.98–188.59, p = 0.027 and OR 215.67; 95 % CI 22.40–2076.04, p = 0.0003. HLA-B*15:02 was not associated with PHT induced SCARs. Significance: An association betweenHLA-B*51:01 and HLA-C*14:02 and PHT induced DRESS and HLA-B*38:02 and PHT induced SJS-TEN has been demonstrated in Thai children.